2010
DOI: 10.1038/nature09464
|View full text |Cite
|
Sign up to set email alerts
|

Identification of UBIAD1 as a novel human menaquinone-4 biosynthetic enzyme

Abstract: Vitamin K occurs in the natural world in several forms, including a plant form, phylloquinone (PK), and a bacterial form, menaquinones (MKs). In many species, including humans, PK is a minor constituent of hepatic vitamin K content, with most hepatic vitamin K content comprising long-chain MKs. Menaquinone-4 (MK-4) is ubiquitously present in extrahepatic tissues, with particularly high concentrations in the brain, kidney and pancreas of humans and rats. It has consistently been shown that PK is endogenously co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
308
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(319 citation statements)
references
References 23 publications
8
308
0
3
Order By: Relevance
“…It is unclear if this was due to a direct effect on the joint tissue as a latter study using menadione-epoxide in the same model was also found to have a significant anti-inflammatory activity [70]. Alternative explanation for these effects includes the possible conversion of these menadione and menadione-epoxide molecules into vitamin K2, as menaquinone-4, through the action of UBIAD1 [68]. This would be consistent with lapine caecal bacterial conversion due to known coprophagy in this species (see chapter by O'Neil et al, in this volume).…”
Section: Menadione and Inhibition Of Inflammationmentioning
confidence: 97%
See 1 more Smart Citation
“…It is unclear if this was due to a direct effect on the joint tissue as a latter study using menadione-epoxide in the same model was also found to have a significant anti-inflammatory activity [70]. Alternative explanation for these effects includes the possible conversion of these menadione and menadione-epoxide molecules into vitamin K2, as menaquinone-4, through the action of UBIAD1 [68]. This would be consistent with lapine caecal bacterial conversion due to known coprophagy in this species (see chapter by O'Neil et al, in this volume).…”
Section: Menadione and Inhibition Of Inflammationmentioning
confidence: 97%
“…Research that started in the 1990s demonstrated that menadione was an important derivative from vitamin K1 that was converted in the rat to make the vitamin K2 congener menaquinone-4 [64][65][66][67]. The enzyme responsible for the conversion of menadione to menaquinone-4, UBIAD1 [68] has a wide distribution across species and likely plays a significant role in the vitamin K status of many animals (see chapter by O'Neil et al, this volume).…”
Section: Menadione and Inhibition Of Inflammationmentioning
confidence: 99%
“…Vitamin K 1 is synthesized by plants, while vitamin K 2 is produced by bacteria [10]. Vitamin K 2 is also synthesized in certain vertebrate tissue through the conversion of vitamin K 1 or phylloquinone into menaquinone-4, a form of vitamin K 2 , using the enzyme UbiA prenyltransferase containing 1 (UBIAD1; [11]). Vitamin K functions as a cofactor for the enzyme gammacarboxylase, which carboxylates glutamic acid and results in its conversion to gamma-carboxyglutamic acid [10].…”
Section: Introductionmentioning
confidence: 99%
“…MK-4 is not commonly synthesized by bacteria and is instead alkylated from menadione, which is supplemented in animal feeds to increase vitamin K levels. In most organs, MK-4 is converted from dietary vitamin K1 and other menaquinones [1,2] via a process catalyzed by UbiA prenyltransferase domain containing protein 1 [3]. Furthermore, MK-4 is prescribed as a therapeutic agent for osteoporosis and to prevent fractures in Japan [4].…”
Section: Introductionmentioning
confidence: 99%